WASTE COLLECTORS FOR EFFECTIVE SOLID WASTE MANAGEMENT - Ms. Mitali Yadav,Dr. Manju Rawat Ranjan,Dr. Satish Shripatrao Deshmukh (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Effective solid waste management has become a critical global challenge, with approximately 2.01billion tons of municipal solid waste generated annually worldwide(1). The exponential growth in wastegeneration, projected to reach 3.8 billion tons by 2050(2), necessitates innovative approaches to waste